2021
DOI: 10.3390/su13158225
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Biogas Production via Co-Digestion of Wastewater Treatment Sewage Sludge and Brewery Spent Grain: Physicochemical Characterization and Microbial Community

Abstract: The present study intends to evaluate a synergy towards enhanced biogas production by co-digesting municipal sewage sludge (SS) with brewery spent grain (BSG). To execute this, physicochemical and metagenomics analysis was conducted on the sewage sludge substrate. The automatic methane potential test system II (AMPTS II) biochemical methane potential (BMP) batch setup was operated at 35 ± 5 °C, pH range of 6.5–7.5 for 30 days’ digestion time on AMPTS II and 150 days on semi-continuous setup, where the organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Since the substrates were gathered over a lengthy span of time, batch studies were also used to verify the activity fluctuation of the substrates. More information on the batch and semi-continuous study arrangement can be found in Mudzanani et al [4].…”
Section: Batch and Semi-continuous Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the substrates were gathered over a lengthy span of time, batch studies were also used to verify the activity fluctuation of the substrates. More information on the batch and semi-continuous study arrangement can be found in Mudzanani et al [4].…”
Section: Batch and Semi-continuous Testsmentioning
confidence: 99%
“…Anaerobic digestion is a well-known biological treatment process that results in the production of valuable methane gas through the degradation and stabilization of municipal sewage sludge [1][2][3]. The need to reduce operating costs, as well as changing standards for the use and disposal of sewage sludge, has sparked interest in more effective sewage sludge treatment processes [4]. One method for increasing efficiency is to physically divide the single-stage anaerobic digestion process into two process stages: a thermophilic pre-treatment stage followed by a mesophilic main treatment stage [5].…”
Section: Introductionmentioning
confidence: 99%